Evaluating Pressure Variability and Influencing Factors during High-Flow Nasal Cannula Therapy in Premature Infants - Fong-Cheng Ho; Chia-Ying Lin; Ane-Shu Chang; Ching-Yi Yeh; Hsiu-Lin Chen (MDPI AG, 2024)
Background: Heated humidified high-flow nasal cannulas (HHHFNCs) are increasingly used as an alternative strategy for weaning from nasal continuous positive airway pressure (NCPAP) in premature infants. However, the optimal pressure provided by HHHFNCs is unknown. This retrospective study investigated the pressure changes and associated factors during HHHFNC therapy in preterm infants. Methods: Clinically stable preterm neonates born with a birth weight of 2500 g or less and receiving HHHFNC therapy for weaning from NCPAP were enrolled. The flow of the HHHNFCs was adjusted to achieve an initial pressure equivalent to the positive expiratory pressure (PEEP) of NCPAP. Subsequent pressure changes in the HHHFNCs were measured by a GiO digital pressure gauge. Results: Nine premature infants were enrolled. Their gestational age (mean ± SD) was 28.33 ± 2.61 weeks, and the birth weight was 1102.00 ± 327.53 g. Overall, 437 pressure measurements were conducted. The median pressure of the HHHFNCs was 5 cmH2O. The generated pressure had a significant association with the body weight, postmenstrual age (PMA) and flow rate. A multiple regression model revealed that the measured pressure (cmH2O) = −5.769 + 1.021 × flow rate (L/min) − 0.797 × body weight (kg) + 0.035 × PMA (days) (r2 = 0.37, p < 0.001). Conclusions: The pressure provided by HHHFNCs is influenced by body weight, PMA, and flow rate. It is feasible to set the delivered pressure of HHHFNCs to match the applied PEEP of NCPAP initially, facilitating the weaning of preterm infants from NCPAP to HHHFNCs.